Something Is Going to Happen Here: The Use of Mandala Art in Enhancing Reflective Practice. (July 2019) - Quinn, Kathleen
Abstract : This article focuses on the use of mandalas as part of a reflective practice journaling process. In this article, there is an approach to the science of communication, empathy, and interdependent communication. Drawing from a previous article on the "space between" in communication spirals, this article uses mandalas as preparation for and instrument of diverse communication. Emphasis is on mandala usage within reflective practice to consider depth interiority and then using the mandala as metaphor for engaging and sharing with others externally in dialogue. How to construct the mandala is included in this article, and there is an exercise for observation and assessment of mandalas. This novel structure for reflective practice supports developing transformational leaders and communication skill through expressive arts, narratives, and stories in journaling. This article considers the function of mandalas, interruptions in communication patterns, mirror neurons, possible paths, and collaborative outcomes for understanding and achieving interprofessional wisdom. This transformational discovery pathway and narrative exercises can be used for creating professional learning communities. This form of reflective practice has innovative possibilities for increased self-awareness and self-care. Included in this article is a list of awareness/mindfulness behaviors to act as a guide and encourage readers to undertake the reflective journaling process. The discovery pathway journal creates a permanent record of thoughts and anchors through the expressive art. The process refers to the Sigma Theta Tau International's Scholarship of Reflective Practice as important to the practice of nursing. Abstract : Supplemental Digital Content is Available in the Text.